Target blood pressure and cardiovascular risk - Dreyfuss-Tubiana, Céline; Sosner, Philippe; Blacher, Jacques (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
An article recently published in the Lancet (1) concerned a meta-analysis of two therapeutic trials ONTARGET (2) and TRANSCEND (3). They were both designed to compare angiotensin receptor blocker (ARB) to angiotensin-converting enzyme (ACE) inhibitors (or their combination) or placebo respectively, to reduce the rate of a composite of cardiovascular death, myocardial infarction (MI), stroke and hospital admission for heart failure, among patients at high risk for cardiovascular events.